PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA APOTEK KURNIA JAYA DI JAKARTA BARAT - Maulana Aziz, Naufal; Haryantini (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the variable price (X1), service quality (X2), purchasing decisions (Y), and the influence of price and service quality on purchasing decisions at the Kurnia Jaya Pharmacy in West Jakarta. This research method uses a quantitative method with an associative approach and the population in this research is 460,056 consumers. The sample used in this research used the entire population of 100 consumers as respondents. In this research, the sampling technique used is non-probability sampling. The results of the Price variable have a significant effect on Purchasing Decisions with a tcount value of 6.845 > ttable 1.661 and a sig value. < 0.05 (0.000 < 0.05). The results of the Service Quality variable have a significant effect on Purchasing Decisions with a calculated t of 6.856 > t table of 1.661 and a sig value. < 0.05 (0.000 < 0.05). The results of the Price and Service Quality variables simultaneously have a significant influence on Purchasing Decisions with a calculated f value of > 35.181 and a sig value of < 0.05 (0.000 < 0.05).